Analysing the Relation between Passion, Motivation, and Subjective Well-Being in Sport: A Systematic Review - Teresa Bento; Anabela Vitorino; Luís Cid; Diogo Monteiro; Nuno Couto (MDPI AG, 2024)
Both the Dualistic Model of Passion and Self-Determination Theory suggest that the persistence of a behaviour over time derives from the internalisation of the passion or motivation that the individual feels about the activity. However, the integration of these theoretical assumptions may lead to a better understanding of related outcomes, in particular on subjective well-being (SWB). In this context, this study aimed at systematically reviewing the relation between passion, behaviour regulation (i.e., self-determined motivation), and SWB in sport. The PRISMA 2020 protocol was used to guide the systematic review. Electronic searches were conducted in the Web of Science database and Pubmed. The following descriptors were used: SWB; passion; motivation; behavioural regulation; and sport. After the search, 12 studies were retrieved for analysis that show us the following results tendencies: harmonious passion (HP) and autonomous motivation (AM) (i.e., more self-determined forms of behaviour regulation) are positively related to SWB (i.e., life satisfaction and positive affect), while obsessive passion (OP) and controlled motivation (CM) (i.e., less self-determined forms of behaviour regulation) are negatively associated with SWB. However, no studies were found to simultaneously analyse the three theoretical constructs. These results show us the importance of developing conditions in sport contexts that promote positive feelings that take into account athletes' development of harmonious passion and self-determined behaviour regulation, in order to achieve higher levels of well-being. Nevertheless, these results also lead us to the necessity for more studies to highlight the theoretical link between passion and motivation in the context of sport, especially regarding the mediating role of motivation in the relationship between passion and well-being.